Pengaruh Kualitas Pelayanan, Harga dan Fasilitas Konsumen Terhadap Minat Berkunjung Kembali Pada Langit Society - Veni Vera Simarmata; Ananda Fitriani Dewi (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This research aims to analyze the influence of service quality, price, and customer facilities on revisit intention at Langit Society. The phenomenon underlying this study is the declining intention of customers to revisit, which is reflected in consumer reviews and preliminary survey results regarding satisfaction with service quality, price, and facilities. This research uses a quantitative method with an associative approach. The population consists of Langit Society customers, with samples taken using the accidental sampling technique, and the number of respondents was determined based on the Lemeshow formula. Data were collected using questionnaires that had been tested for validity and reliability. Data analysis techniques employed multiple linear regression with the assistance of SPSS to determine both partial and simultaneous influences of each variable. The results show that service quality has a positive and significant effect on revisit intention. Price also has a significant effect, although its influence is relatively smaller compared to service quality. Customer facilities also positively and significantly affect revisit intention, emphasizing the importance of comfort and physical support for visitors. Simultaneously, the three variables have a positive and significant effect on revisit intention at Langit Society. These findings highlight the necessity of improving service quality, setting competitive prices, and enhancing facilities as strategies to maintain customer loyalty.